2016
DOI: 10.1007/s11356-016-8079-x
|View full text |Cite
|
Sign up to set email alerts
|

A review and investigation of the effect of nanophotocatalytic ozonation process for phenolic compound removal from real effluent of pulp and paper industry

Abstract: Phenol and its derivatives are the major environmental pollutants discharged from paper and pulp industries into water bodies. All these compounds and chlorinated phenolic compounds in particular are very toxic to fauna and flora, even at relatively low concentration. This study aimed to investigate the removal rate of phenolic compounds from the effluent of pulp and paper industries using a combination of ozonation and photocatalytic processes. Firstly, a certain volume from the effluent of paper and pulp ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 69 publications
0
31
0
2
Order By: Relevance
“…Considering the fact that, according to the studies conducted within the past 10-20 years, the presence of this compound has shown an increasing trend in drinking water sources, they must be removed from drinking water sources before the disinfection process [19,23,24]. Chemical coagulation, precipitation, oxidation, adsorption, ion exchange and filtration by membranes may be named as some of the methods of the removal of these compounds from aqueous media [25][26][27][28][29]. In this regard, removal of these contaminants by electrochemical process has attracted wide attention in different fields of water and wastewater treatment [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the fact that, according to the studies conducted within the past 10-20 years, the presence of this compound has shown an increasing trend in drinking water sources, they must be removed from drinking water sources before the disinfection process [19,23,24]. Chemical coagulation, precipitation, oxidation, adsorption, ion exchange and filtration by membranes may be named as some of the methods of the removal of these compounds from aqueous media [25][26][27][28][29]. In this regard, removal of these contaminants by electrochemical process has attracted wide attention in different fields of water and wastewater treatment [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…This issue threatens the health and safety of citizens in developing countries at macro levels of management due to the inability to fully control water purification and the crisis of non-sanitary problems [9][10][11][12]. Removing suspended particles and colloids is one of the most significant stages of water purification that is performed during the set of processes and operations, including coagulation, flocculation, and sedimentation [13][14][15]. High water turbidity can cause microorganisms to be maintained against the effect of antiseptic substances and lead to the growth of bacteria, as well as increase the amount of needed antiseptic substances.…”
Section: Introductionmentioning
confidence: 99%
“…The hydroxyl radicals may be produced by means of various chemical, photochemical, sonochemical or electrochemical reactions [6]. Among these methods, the photochemical processes, especially heterogeneous photocatalytic process involving semiconductors and ultraviolet (UV) irradiation, such as TiO 2 /UV, Fe 2 O 3 -TiO 2 /UV, ZnO/UV, ZnO/O 2 /UV and TiO 2 /H 2 O 2 /UV, have attracted significant attention in the degradation of lignin [7][8][9][10]. Wide band gap semiconductors, such as TiO 2 and ZnO, are employed due to their high valence band potentials.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 and ZnO generally photogenerate holes with potentials higher than the redox potential of H 2 O/·OH, favoring the production of hydroxyl radicals. The introduction of H 2 O 2 or O 2 in photocatalytic processes generally further improves the photocatalytic performance of TiO 2 or ZnO by either trapping photogenerated electrons to suppress the recombination of photogenerated electrons and holes or by accepting electrons to produce additional hydroxyl radicals [10,11]. Because semiconductors can only be excited by light with energy greater than their band gaps, UV light has to be used as the excitation source for TiO 2 and ZnO with band gaps wider than 3.0 eV.…”
Section: Introductionmentioning
confidence: 99%